Engaging Cooperative Research. (September 2014) - Hinchliffe, Steve; Levidow, Les; Oreszczyn, Sue
Cooperative research involves upstream engagement of practitioners, introducing diverse knowledges and expertise in ways that can, in theory at least, generate new knowledge that is socially robust and publicly accountable. And yet, judging cooperative research solely in terms of accountability may underplay the transformative and nonaccountable/nonconvergent nature of research—the production, in other words, of the new when collectives are drawn together. Using examples from research that sought to provide environmental civil society organisations (CSOs) with the resources to shape cooperative research, this paper argues that cooperative research may not simply mark an extension of public engagement with science but can also seed an anticipatory and thus creative research process. For cooperative research to play this role there is a need to highlight the human and nonhuman attachments that underpin cooperative research activity. We argue that such activity might best have as its aim the empowerment, not simply of participants, but of the political situations that CSOs can help to foment.